2009
DOI: 10.1021/jp902505r
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Phase Evolution in Mg1−xAlxB2 (0 < x < 0.5) and Its Experimental Signatures

Abstract: USA andersson @Ianl.gov RECEIVED DATE CORRESPONDING AUTHOR FOOTNOTEDespite the chemical and structural simplicity of MgB2' at 39 K this compound has the highest known Tc of any binary compound. Electron doping by substituting Al for Mg leads to decreasing Tc and the observed concentration dependent rate of decrease has been proposed to arise from the non-ideal character of MgB2-AIB2 solid solutions, which derives from the existence of an ordered M~.sAlo.sB2 compound. Heterogeneous nano-scale structure patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…The most incisive example is the demonstration within the data presented here that a crystalline material can contain tens of percents of a second ordered structure that is clearly visible in local structure measurements but that may not (or may) display a diffraction pattern accompanying that of the host, indicating the importance of the morphology of its domains on the nanometer scale. Motivated by this finding, we discovered via modeling ,, , that this is not a difficult feat. However, insofar as the concept of nanoscale heterogeneity and its origin in the collective behavior of defects in a host lattice is relatively new, a number of issues remain.…”
Section: Resultsmentioning
confidence: 97%
“…The most incisive example is the demonstration within the data presented here that a crystalline material can contain tens of percents of a second ordered structure that is clearly visible in local structure measurements but that may not (or may) display a diffraction pattern accompanying that of the host, indicating the importance of the morphology of its domains on the nanometer scale. Motivated by this finding, we discovered via modeling ,, , that this is not a difficult feat. However, insofar as the concept of nanoscale heterogeneity and its origin in the collective behavior of defects in a host lattice is relatively new, a number of issues remain.…”
Section: Resultsmentioning
confidence: 97%
“…The material is therefore heterogeneous-containing multiple ordered structures-on the nanometer scale at or below the diffraction limit. Addressing the putative contradiction in this concept, that a material could contain tens of percents of a second ordered structure that would not give an unambiguous signal in diffraction, delayed detailed reporting of these results [20,21] while we undertook an extensive evaluation of local order and heterogeneity [38][39][40][41]43,44], ultimately finding that this type of behavior was easily produced because of the limitations of crystallography. Arguing this attribute of the structure by claiming that, for example, scattering, photoemission, microscopy, and ultrasound data contradict it ignores the fact that all experimental methods are limited to their intrinsic length and timescales.…”
Section: Discussionmentioning
confidence: 99%
“…A corollary to this type of distribution would be that, if these probabilities are different in different directions, small tetragonal or orthorhombic distortions will occur [23,65]. We have shown that, if differently oriented domains of chemically ordered structures are coherent at their interfaces, then the expected splitting of the diffraction peaks will not occur because the strain is distributed over all of the atoms, and the distortion is averaged out over the entire crystal [43,44]. Breaking this registry at the interfaces, such as might occur during the initiation of the martensitic transformation or from radiation damage, allows the domains to relax and exhibit their lower symmetries while concomitantly stabilizing the dislocations or other types of defects [43].…”
Section: E Trends In the Local Structure With Ga Concentration And Tmentioning
confidence: 99%
See 2 more Smart Citations